Optimal Planning For Purchase and Storage with Multiple Transportation Types for Concentrated Latex under Age-Dependent Constraint - Tuanjai Somboonwiwat; Walailak Atthirawong; Sutthinee Klomsae (My University, 2019)
This paper presents the mathematical model to support decision planning over the multi-period for purchasing storage and transportion of concentrated latex for the rubber glove production under age-dependent constraint. The model considers multiple suppliers with different purchasing costs, varying product ages, multi-truck load capacity and costs, and storage times with respect to perishable product. The model is then applied to a rubber glove production case study and the sensitivity analysis is performed. The result reveals that the price of concentrated latex in each period and truck load capacity decision are critical factors for total cost reduction.
Keywords: Optimization and Mathematical Programming